Challenges in the development of green and sustainable software for software multisourcing vendors: Findings from a systematic literature review and industrial survey. Issue 8 (5th February 2018) - Salam, Muhammad; Khan, Siffat Ullah
Abstract: Green and sustainable software development has emerged in recent years, and vendors are constantly striving to develop software that has a less hazardous impact on the environment, economy, and human beings. However, developing green software in the context of software multisourcing is not a risk‐free activity, and vendors are exposed to several challenges. The authors have conducted both a systematic literature review and an industrial survey to identify the challenges faced by multisourcing vendors in the development of green and sustainable software. The final publication sample for the systematic literature review is composed of 54 research papers. Similarly, the final sample of the industrial survey is composed of 108 relevant experts. The authors have identified a list of 14 challenges. Of these challenges/risk factors, 8 have been tagged as critical risk factors. These critical risk factors are "lack of green RE practices, " "high power consumption, " "high carbon emission throughout the software development, " "poor software design (architectural, logical, physical, and user interface), " "lack of ICTs for coordination and communication, " "high resource requirements, " "lack of coding standards, " and "lack of green software development knowledge."